MiR‐21 improves invasion and migration of drug‐resistant lung adenocarcinoma cancer cell and transformation of EMT through targeting HBP1 - Chongyu Su; Xu Cheng; Yunsong Li; Yi Han; Xiaoyun Song; Daping Yu; Xiaoqing Cao; Zhidong Liu (Cancer Medicine)
Abstract This study was aimed at the investigation of the effects of miR‐21 on drug resistance, invasion, migration, and epithelial–mesenchymal transition (EMT) of lung adenocarcinoma cells and the related molecular mechanisms. Cell viability of A549 cell line was measured by MTT assay. Wound healing assay and transwell assay were, respectively, employed to examine cell migration and invasion abilities. The cells were transfected with miR‐21 mimic or inhibitor using Lipofectamine 3000. The target relationship between miR‐21 and HBP1 was confirmed by luciferase reporter gene assay. Western blot and qRT‐PCR were used to examine the expression of HBP1 and EMT‐related molecules. Compared with A549 cells, drug resistance of A549/PTX cells and A549/DDP cells were obviously stronger. A549/PTX cells and A549/DDP cells had stronger ability of migration and invasion compared with parental A549 cells. Meanwhile, EMT of A549/PTX and A549/DDP was significantly higher than that of A549 cells. MiR‐21 promoted migration, invasion, and EMT of human lung adenocarcinoma cancer cells. Our experiment also verified the target relationship between miR‐21 and HBP1. MiR‐21 may affect migration and invasion ability of drug‐resistant lung adenocarcinoma cells by targeting HBP1, therefore modulating EMT.